The Influence of Temperature and Storage Time on Alcohol Content of Pineapple Infused Arak Bali - Ratih, Gusti Ayu Made; Suryaningsih, Putu Ayu (International Journal of Natural Science and Engineering, 2023)
The development of gastronomic drinks from local cultures is an interesting potential, especially in terms of traditional drinks such as Balinese Arak. However, the sustainability of alcoholic beverage products such as Arak Bali can be affected by various factors, including temperature and storage time. This study aims to investigate the effect of temperature and storage time period on alcohol content in Balinese Arak infused with pineapple. This study used the Quasi Experimental method with a Complete Randomized Design (RAL) design of 2 factors, namely temperature factors and storage time factors. The results of the analysis showed that the Methanol content in the Bali Arak sample had negative results. In samples stored at 1ºC–8ºC for 7, 14, 21, and 28 days, the Ethanol content ranged from 16.38% to 17.27%. Meanwhile, samples stored at temperatures of 24ºC–30ºC during the same period had Ethanol content ranging from 17.27% to 20.49%. The results of statistical analysis using Two Way Anova show that there is a significant influence of temperature and storage time on alcohol content in Balinese Arak infused with pineapple. The results of this study provide further understanding of the factors that influence the stability and characteristics of traditional drinks such as Balinese Arak, and can be a guide in the development of sustainable and quality alcoholic beverage products.